2014
DOI: 10.1007/s00894-014-2436-9
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on cooperativity of pnicogen bonds

Abstract: Substituent effects on cooperativity of P···N pnicogen bonds are studied in XH2P···NCH(2)P···NCY (X=F, Cl; Y=H, F, CN, OH, NH(2)) complexes using high-level ab initio calculations. An increased attraction or a positive cooperativity is observed on introduction of a third molecule to the XH(2)P···NCH(2)P and NCH(2)P···NCY dyads. The shortening of the each pnicogen bond distance in the triads is dependent on the strength of the P···N bond and is increased in the order Y = NH(2) > OH > H > F > CN. The energy deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Traditionally, the positive and negative signs of the local minimum and maximum of the electrostatic potential ( V S,min and V S,max , respectively) have been invoked to characterize the positive and negative sites on the molecular surfaces, respectively [33,41,42,43,44,45]. Note that the sign and magnitude of potential on the electrostatic surface of a main group atom M along the outer portion of the R–M bond extension is generally used to characterize the nature and quantify the strength and size of its σ-hole, respectively [42,43,44,45,46,47]. The larger the V S,max associated with a site on M, the stronger its interaction with the Lewis base might be [43,46,47].…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the positive and negative signs of the local minimum and maximum of the electrostatic potential ( V S,min and V S,max , respectively) have been invoked to characterize the positive and negative sites on the molecular surfaces, respectively [33,41,42,43,44,45]. Note that the sign and magnitude of potential on the electrostatic surface of a main group atom M along the outer portion of the R–M bond extension is generally used to characterize the nature and quantify the strength and size of its σ-hole, respectively [42,43,44,45,46,47]. The larger the V S,max associated with a site on M, the stronger its interaction with the Lewis base might be [43,46,47].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Note that the sign and magnitude of potential on the electrostatic surface of a main group atom M along the outer portion of the R–M bond extension is generally used to characterize the nature and quantify the strength and size of its σ-hole, respectively [42,43,44,45,46,47]. The larger the V S,max associated with a site on M, the stronger its interaction with the Lewis base might be [43,46,47]. Whereas the choice of an isodensity envelope is arbitrary [33,48], we used the 0.001 au isodensity envelope on which to compute the electrostatic potential.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The latter results unequivocally demonstrate that the local most VS,max values associated with O's s-hole in isolated monomers cannot be used as a universal descriptor of intermolecular interactions, or a measure of complex stability. This is arguably because the dependence between VS,max and DE has previously been demonstrated to be linear in some systems, 22,[84][85][86] but observed not to be so in the complexes reported in this study. This suggests that the Coulombic view of explaining the origin of intermolecular interactions in the complexes examined in this study is incomplete, and such a view is not applicable to all systems as is not universal.…”
Section: Second-order Donor-acceptor Charge Transfer Delocalization F...mentioning
confidence: 49%
“…Previous studies have shown that the QTAIM analysis is very helpful tool for studying the cooperative effects between noncovalent interactions . Considering the linear relationship between the strength of an interaction and electron density ( ρ BCP ) at the corresponding bond critical point (BCP), an increase in the ρ BCP values at the B⋅⋅⋅N and M⋅⋅⋅N BCPs of the ternary complexes with respect to the binary systems can provide another evidence for the strengthening of these interactions.…”
Section: Resultsmentioning
confidence: 99%